2020
DOI: 10.1371/journal.pntd.0008955
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the knockdown resistance (kdr) mutations in the head lice (Pediculus humanus capitis) collected from primary school children of Thailand

Abstract: Human head lice are blood-sucking insects causing an infestation in humans called pediculosis capitis. The infestation is more prevalent in the school-aged population. Scalp itching, a common presenting symptom, results in scratching and sleep disturbance. The condition can lead to social stigmatization which can lead to loss of self-esteem. Currently, the mainstay of treatment for pediculosis is chemical insecticides such as permethrin. The extended use of permethrin worldwide leads to growing pediculicide re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Most likely this mutation could have been missed during most of the surveys due to selective genotyping/sequencing targeting three known kdr mutations. In most of the studies involving DNA sequencing, L1014 locus was not covered (Brownell et al, 2020; Durand et al, 2007; Firooziyan et al, 2017; Ghahvechi Khaligh et al, 2021; Komoda et al, 2020; Larkin et al, 2020; Ponce-Garcia et al, 2017; Roca-Acevedo et al, 2019; Toloza et al, 2014; Drali et al, 2012). It is therefore suggested that in all future studies, this mutation may be taken into account during sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely this mutation could have been missed during most of the surveys due to selective genotyping/sequencing targeting three known kdr mutations. In most of the studies involving DNA sequencing, L1014 locus was not covered (Brownell et al, 2020; Durand et al, 2007; Firooziyan et al, 2017; Ghahvechi Khaligh et al, 2021; Komoda et al, 2020; Larkin et al, 2020; Ponce-Garcia et al, 2017; Roca-Acevedo et al, 2019; Toloza et al, 2014; Drali et al, 2012). It is therefore suggested that in all future studies, this mutation may be taken into account during sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…kdr -type gene mutations cause the poor efficacy of permethrin. Three kdr -type point mutations (M815l, T917l, and L920F) in the VGSC α-subunit gene are associated with permethrin-resistant phenotypes responsible for kdr -type resistance [ 13 - 15 ]. These kdr mutant alleles have been found worldwide [ 10 ], and they are most prevalent in countries with easy access to pediculicidal agents [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uruguay, the UK, and Australia exhibited kdr allele frequencies of 100%, while the USA, Argentina, Brazil, Denmark, the Czech Republic, Egypt, and Israel exhibited kdr allele frequencies between 11% and 97%. Regarding primary school children in Thailand, kdr T9171 and L920F point mutations were discovered in permethrin-resistant head lice [ 13 ]. In Honduras [ 14 ], Chile [ 15 ], and Madagascar [ 16 ], the T917I kd r allele was found in head lice resistant to pyrethroid insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…The female louse may mate and start laying viable eggs approximately 1.5 days after becoming an adult. Unless treated, the cycle repeats itself roughly every three weeks (6).…”
Section: Introductionmentioning
confidence: 99%